Experiment study on the influencing factors of mechanical response of HMX-based PBXs in the high-g deceleration environments. Issue 1 (2nd January 2021) - Xu, Wenzheng; Liang, Xin; Li, Hao; Deng, Jie; Guo, Fengwei; Li, Yuexin; Yan, Tianlun; Wang, Jingyu
ABSTRACT: An impact test method was designed to study the mechanical behaviors of explosive charges in deceleration environments. With this method, the deformation and density variation of explosive charges in various deceleration environments can be obtained by changing the decelerations. The deceleration can be precisely changed without changing the strength of target and the speed of projectile. The high-g deceleration environment was simulated by this method. Then, the factors which influence the mechanical response of cyclotetramethylenete-tranitramine (HMX)-based polymer-bonded explosives (PBXs) in the high-g deceleration environments were investigated. The variation of density, macro size, and meso-damage was obtained. The results showed that the initial density, binder type, and particle size have different effects on the deceleration resistance of HMX-based PBXs, then the mechanism was discussed. The shock sensitivities of the PBXs with different densities, binders, and particle sizes were tested. The relationship between the shock wave safety and the deceleration resistance was discussed.